DIAGNOSIS AND TREATMENT OF PATIENTS WITH SEVERE HYPERCHOLESTEROLEMIA IN REAL OUTPATIENT PRACTICE (ACCORDING TO THE RECVASA REGISTRY) - A. I. Ershova; A. N. Meshkov; S. S. Yakushin; M. M. Loukianov; K. A. Moseychuk; S. Yu. Martsevich; A. V. Zagrebelnyy; A. N. Vorobyev; K. G. Pereverzeva; E. A. Pravkina; A. N. Kozminskiy; S. A. Boytsov (Рациональная фармакотерапия в кардиологии, 2015)
Hypercholesterolemia is a proven risk factor for atherosclerotic cardiovascular diseases and for their complications.Aim. To assess the quality of diagnosis and treatment of patients with severe hypercholesterolemia (total cholesterol >6.2 mmol/L) in the real outpatient practice.Material and methods. All patients with a diagnosis of arterial hypertension, ischemic heart disease, chronic heart failure, atrial fibrillation applied to primary care physicians or cardiologists in one of the randomly selected out-patient clinic of Ryazan in March-May 2012 and included into the RECVASA registry were enrolled into the study group (n=1642).Results. The group of patients with severe hypercholesterolemia consisted of 561 (44%) patients at the age of 67 (59-75) years [Me (25% -75%)]. At that, diagnosis of hyperlipidemia was indicated only in 9% of outpatient cards. Data of one or more blood chemistries including low density cholesterol (LDC) levels were presented only in 7% of outpatient cards. 83.7% of patients with severe hypercholesterolemia were classified as patients at high or very high cardiovascular risk, but statins were recommended only to 17.8% of them. Statins were mainly recommended in moderate doses; only one patient took atorvastatin 40 mg per day. Blood LDC levels were examined only in 5% of patients during statins therapy; nobody of them reached target LDC levels.Conclusion. The study data revealed the presence of a high prevalence of severe hypercholesterolemia in patients with cardiovascular diseases and poor quality of diagnosis and treatment in these patients in the real outpatient practice.